PENGARUH LINGKUNGAN SEKOLAH DALAM MEMBENTUK KEPRIBADIAN SISWA DI ERA MODERN - Adinda Rahmawati; Linda Ade Rahmawati; Ainun Rahmawati; Anis Kirana Lestari; Ira Nur Fakhira; Rehan Adittya Ramadhan (Education First Journal, 2026)
The purpose of this study is to examine the influence of the school environment on the personality development of elementary school students. A conducive school environment, supported by school culture, teacher role models, principal leadership, and the use of learning technology, plays an important role in instilling character values such as discipline, responsibility, and tolerance. In addition, support from families and the community strengthens students’ character development. However, the modern era also presents challenges in the form of shifting values. Therefore, adaptive character education through synergy among schools, families, and the social environment is needed. Such synergy is the key to shaping elementary school students with noble character who are prepared to face the challenges of the modern era. Modernization and technological development bring both positive impacts and challenges to character formation in elementary school students. This study also aims to examine the influence of the educational environment (family, school, and community) and discipline on students’ character development and learning motivation in the modern era.